First report of Evelineus mcintoshii (Langerhans, 1880) (Heteronemertea, Lineidae) from the Mediterranean Sea - HOFFMAN, RAZY; KAJIHARA, HIROSHI (Mediterranean Marine Science, 2020)
The ribbon worm Evelineus mcintoshii is reported for the first time from the Mediterranean Sea. Observations that took place, during two algal surveys, on the intertidal abrasion platforms at the middle of the Levantine Sea of Israel indicated that this species is hiding inside a mixture of local and non-indigenous marine seaweeds. It is probably another alien species, one of many, that adopted the Levantine basin of the Eastern Mediterranean due to tropical environmental conditions that characterize this sea. We discuss the first record of this species and its possible origins as well as the first report of Notospermus geniculatus, the other marine nemertean species recently reported from Israel.